2019
DOI: 10.1590/1414-431x20197728
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of lncRNA HULC knockdown on rat secreting pituitary adenoma GH3 cells

Abstract: Pituitary adenoma is one of the most common tumors in the neuroendocrine system. This study investigated the effects of long non-coding RNAs (lncRNAs) highly up-regulated in liver cancer (HULC) on rat secreting pituitary adenoma GH3 cell viability, migration, invasion, apoptosis, and hormone secretion, as well as the underlying potential mechanisms. Cell transfection and qRT-PCR were used to change and measure the expression levels of HULC, miR-130b, and FOXM1. Cell viability, migration, invasion, and apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Overexpression of a subgroup of long noncoding RNAs, termed “highly up-regulated in liver cancer” (HULC), promoted GH3 cell viability, migration, invasion, and PRL and GH secretion with knockdown inducing apoptosis ( 286 ).…”
Section: Epigenetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
“…Overexpression of a subgroup of long noncoding RNAs, termed “highly up-regulated in liver cancer” (HULC), promoted GH3 cell viability, migration, invasion, and PRL and GH secretion with knockdown inducing apoptosis ( 286 ).…”
Section: Epigenetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
“…Therefore, it is important to clarify which factors affect the secretory mechanism of GH. Many studies have reported that miRNAs can affect GH secretion [ 35 , 56 , 57 ]. However, research on circRNAs that regulate GH secretion, especially circRNAs that act as molecular sponges of miRNAs, is rare.…”
Section: Discussionmentioning
confidence: 99%
“…HULC suppresses Beclin-1 phosphorylation, thus reducing autophagy, via the mTOR pathway (19). Knockdown of HULC inhibits pituitary adenoma GH3 cells via the up-regulation of miR-130b, the down-regulation of Forkhead box M1 (FOXM1), and the activation of the phosphoinositide-3kinase/serine-threonine kinase Akt/mammalian target of rapamycin (PI3K/Akt/mTOR) and Janus kinase-1 (JAK1)/ signal transducer and activator of transcription-3 (STAT3) pathways (20). These results demonstrated that HULC knockdown inhibited HepG2 cells proliferation and invasion abilities in vitro, as well as tumor growth in vivo, and promoted the survival of the mice.…”
Section: Discussionmentioning
confidence: 99%